Fiscal decentralization and regional disparities in Czechia and Slovakia: Regression analysis at the NUTS2 and NUTS3 level - Maličká, Lenka (University of Pardubice, 2019)
Connection between fiscal decentralization and regional disparities is usually explained in two different manners. Fiscal decentralization might enhance the economic growth and optimal public good provision (and by this way might reduce regional disparities) or it can contribute to the deepening of differences among poor and rich regions. However, there is a wide empirical research of this connection in the economic literature. Despite it, in Czech and Slovak related research, there is an absence of such a literature. This paper focuses on revealing the character of relationship between fiscal decentralization and regional disparities in Czechia and Slovakia on both NUTS2 and NUTS3 levels. Regional disparities increase within both countries. Additionally, estimations results are about supporting the undesirable effect of fiscal decentralization. Statistical significant positive relationship between expenditure and revenue decentralization and regional disparities is observed in both countries, while this relationship using the measurement of tax decentralization is significant and negative only in the case of Slovakia. Unfortunately, even if the inverse estimated relationship support the hypothesis about reduction of regional disparities by tax decentralization, analysis of input data shows the trend toward decreasing the tax decentralization. It contributes to higher regional disparities, too.
Keywords: regional disparities; fiscal decentralization; NUTS 2; NUTS 3; R12; H71; H73